Characteristics of rumen microbiota and Prevotella isolates found in high propionate and low methane-producing dairy cows - Shinkai, Takumi; Takizawa, Shuhei; Enishi, Osamu; Higuchi, Koji; Ohmori, Hideyuki; Mitsumori, Makoto (Frontiers in Microbiology, 2024)
Ruminal methane production is the main sink for metabolic hydrogen generated during rumen fermentation, and is a major contributor to greenhouse gas (GHG) emission. Individual ruminants exhibit varying methane production efficiency; therefore, understanding the microbial characteristics of low-methane-emitting animals could offer opportunities for mitigating enteric methane. Here, we investigated the association between rumen fermentation and rumen microbiota, focusing on methane production, and elucidated the physiological characteristics of bacteria specific to found in low methane-producing cows. Thirteen Holstein cows in the late lactation stage were fed a corn silagebased total mixed ration (TMR), and feed digestion, milk production, rumen fermentation products, methane production, and rumen microbial composition were examined. Cows were classified into two ruminal fermentation groups using Principal component analysis: low and high methaneproducing cows (36.9 vs. 43.2 L/DMI digested) with different ruminal short chain fatty acid ratio [(C2+C4)/C3] (3.54 vs. 5.03) and dry matter (DM) digestibility (67.7% vs. 65.3%). However, there were no significant differences in dry matter intake (DMI) and milk production between both groups. Additionally, there were differences in the abundance of OTUs assigned to uncultured Prevotella spp.sp., Succinivibrio, and other 12 bacterial phylotypes between both groups. Specifically, a previously uncultured novel Prevotella sp. with lactate-producing phenotype was detected, with higher abundance in low methane-producing cows. These findings provide evidence that Prevotella is may be associated with low methane and high propionate production. However, further research is required to improve the understanding of microbial relationships and metabolic processes involved in the mitigation of enteric methane.